2009
DOI: 10.1186/1471-2318-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Current experiences and educational preferences of general practitioners and staff caring for people with dementia living in residential facilities

Abstract: Background: Residential care is important for older adults, particularly for those with advanced dementia and their families. Education interventions that achieve sustainable improvement in the care of older adults are critical to quality care. There are few systematic data available regarding the educational needs of Residential Care Facility (RCF) staff and General Practitioners (GPs) relating to dementia, or the sustainability of educational interventions. We sought to determine participation in dementia ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…We found that teamwork, communication and leadership were consistently recognised as key elements of organisational culture which potentially influence staff and resident outcomes in care facilities [2]. Other empirical evidence supports these findings, showing that management behaviour (such as the extent of open communication patterns and relationship-oriented leadership behaviour) is associated with resident outcomes [6].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found that teamwork, communication and leadership were consistently recognised as key elements of organisational culture which potentially influence staff and resident outcomes in care facilities [2]. Other empirical evidence supports these findings, showing that management behaviour (such as the extent of open communication patterns and relationship-oriented leadership behaviour) is associated with resident outcomes [6].…”
Section: Introductionsupporting
confidence: 67%
“…Residential care is an important component of service delivery for older people with complex health problems, particularly severe dementia [1]. Costs, staff shortages, staff turnover and communication problems are cited as barriers to sustainable improvements in the care of people living in residential care facilities [2]. Although educational interventions in residential care may be evaluated positively by participants [3], we found evidence that impact on residents may be restricted by limited staff participation [4].…”
Section: Introductionmentioning
confidence: 87%
“…However our data confirm that, despite staff and GPs working in residential care frequently participating in education and generally perceiving their knowledge as good, perceived educational needs persist [16]. The most effective way to translate the available evidence to practice is not clear and there is a paucity of prospective data to guide practice.…”
Section: Introductionmentioning
confidence: 56%
“…It is also recognised that, although the residential aged care sector is often discussed as a homogeneous entity, there is considerable variability in culture and needs, highlighting the importance of identifying local barriers and solutions in any change project. Our previous work also identified the preferred format for interventions in RACF. Small group approaches which are flexible, practical and case‐based were sought.
I think if you do give the people the opportunity to brainstorm solutions for their own problems they're usually very good.
…”
Section: Introductionmentioning
confidence: 99%